Bain al-Daulah wa al-Dîn: Ma'sâh al-Jamâ'ât al-Mutatarrifah fî 'Asr al-Hukm al-Jadîd (Orde Baru) - Syukur, Abdul (Studia Islamika, 2001)
In the Indonesian context, the discourse regarding the relationship between religion and state is always coloured by the struggle between groups that wants to implement Shari'ah (Islamic Law) as the state ideology on the one hand, and nationalist groups that resist it on the other.The appearance from time to time of Islamic groups in Indonesia that want to implement Shari'ah as the state ideology is understandable given that the majority of the community are Muslims. The deliberation on the form and instituation around Shari'ah in Indonesia is generally set in the context of the choosing the best system of governance.DOI: 10.15408/sdi.v8i3.683